(untitled) (European Journal of Multidisciplinary Studies, 2017)
Communication is a complex process and an important element of human activity. Communication is an act of transfering data and information from one person to another person and also a skill that is learned through life. By different authors there are different definitions and descriptions of the communication process. Presented in this paper is the importance of the communication process leader during leadership, effective communication factors, ineffective and communication. Leader during the leadership uses different ways of communication are covered: Interviews, communication with two or more people, meetings, meetings, masiv- media communication, public communication, etc. Organizing meetings during the show director community must correctly, be prepared and be a good example for others.